Analysis of waste in the flow process warehouse using the lean warehousing method at ABC Company - Pamungkas, Catur Arta; Aryanny, Enny (Operations Excellence: Journal of Applied Industrial Engineering, 2025)
ABC Company is a manufacturing company that produces animal feed using raw materials stored in a warehouse. One type of raw material that is widely used for animal feed production needs is the premix type of raw material in warehouse 1. The large number of raw material needs makes warehouse activities increase. The large number of activities causes the warehouse to often experience wasteful activities with a lead time exceeding the company's standard of 420 minutes. This waste can reduce the effectiveness and efficiency of the warehousing flow process. Therefore, the purpose of this study is to determine what waste occurs in the warehouse using the lean warehousing method and to provide suggestions for improvements with Plan, Do, Check, Action and Seiri, Seiton, Seiso, Seiketsu, Shitsuke. Analysis carried out using the lean warehousing method is important for the category of activities that add value, the category of activities that are needed, the category of activities that are not needed, and the time of warehousing flow can be known through value stream mapping both before and after improvement. From the analysis conducted, it was found that there were 52 warehouse flow activities with an activity time of 556 minutes, which after being given a proposal for improvement in the warehouse flow process activities decreased to 39 activities with a lead time of 304 minutes.